2015
DOI: 10.1007/s00253-015-7229-2
|View full text |Cite
|
Sign up to set email alerts
|

A stable luciferase reporter plasmid for in vivo imaging in murine models of Staphylococcus aureus infections

Abstract: In vivo imaging of bioluminescent bacteria permits their visualization in infected mice, allowing spatial and temporal evaluation of infection progression. Most available bioluminescent strains were obtained by integration of the luciferase genes into the bacterial chromosome, a challenging and time-consuming approach. Recently, episomal plasmids were used, which were introduced in bacteria and expressed all genes required for bioluminescence emission. However, the plasmid was progressively lost in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…With the purpose of evaluating fhuD2 promoter activity in vitro and in vivo, we used a reporter plasmid, pMABA-Par/TA-P fhuD2 -lux, with the lux operon of Photorhabdus luminescens under the control of the 213-bp upstream region of the gene containing the fhuD2 promoter from the S. aureus Newman strain. The plasmid had been molecularly engineered to be stably maintained in vitro and in vivo in the absence of selective antibiotic pressure (21).…”
Section: Resultsmentioning
confidence: 99%
“…With the purpose of evaluating fhuD2 promoter activity in vitro and in vivo, we used a reporter plasmid, pMABA-Par/TA-P fhuD2 -lux, with the lux operon of Photorhabdus luminescens under the control of the 213-bp upstream region of the gene containing the fhuD2 promoter from the S. aureus Newman strain. The plasmid had been molecularly engineered to be stably maintained in vitro and in vivo in the absence of selective antibiotic pressure (21).…”
Section: Resultsmentioning
confidence: 99%
“…This plasmid is derived from the pFN10 family of Francisella shuttle vectors carrying orf4 and orf5 (31). Based on the homology of orf5 with the axe (32) and phd (33) antitoxins, orf4 and orf5 are thought to encode components of a plasmid addiction system which likely improve plasmid retention in vivo and in vitro (13). In this study, the concentration of bacteria required to generate a detectable signal in vivo was relatively high, which may have limited the detection of bacteria very early in infection.…”
Section: Discussionmentioning
confidence: 99%
“…Pivotal experiments by Contag et al have demonstrated the usefulness of BLI in the noninvasive study of bacterial pathogenesis and the evaluation of antibiotic treatments for Salmonella enterica serovar Typhimurium (11). Subsequently, bioluminescent reporters have been introduced into other bacteria, including Mycobacterium tuberculosis (10,12), Staphylococcus aureus (13,14), Burkholderia mallei (15), and Yersinia pestis (16,17). Further, BLI has been used to evaluate vaccines (18), antibiotics (19)(20)(21), and supportive therapies (22) for a range of pathogens.…”
mentioning
confidence: 99%
“…Gene expression can be measured by cloning a promoter of interest upstream of the lux operon, and interpreting the bioluminescence from bacteria containing such constructs as a measure of transcription [ 3 , 4 ]. This provides a reporter that can measure gene expression at high frequency and with less background noise than other reporters, such as GFP [ 4 , 5 ], and has found great value in both bacteria [ 6 ] and eukaryotes [ 7 ], with important recent applications in whole cell biosensors [ 8 ], live animal infection models [ 9 , 10 ] and live tumour infection models [ 11 ].…”
Section: Introductionmentioning
confidence: 99%